Association between physical activity, growth differentiation factor 15 and bodyweight in older adults: A longitudinal mediation analysis. Issue 2 (20th January 2023) - Raffin, Jérémy; Rolland, Yves; Parini, Angelo; Lucas, Alexandre; Guyonnet, Sophie; Vellas, Bruno; de Souto Barreto, Philipe; ,
Abstract: Background: Late‐life aging is often associated with appetite reduction and weight loss. Physical activity (PA) may prevent these processes, but the molecular mechanisms involved remain elusive. The present study investigated the putative mediating aspect of growth differentiation factor 15 (GDF‐15), a stress signalling protein involved in aging, exercise and appetite control, on the association between PA and late‐life‐associated weight loss. Methods: One thousand eighty‐three healthy adults (63.8% women) aged 70 years and over who participated in the Multidomain Alzheimer Preventive Trial were included. Bodyweight (kg) and PA levels (square root of metabolic equivalent of task‐min/week) were assessed repeatedly from baseline to the 3‐year visit, whereas plasma GDF‐15 (pg/mL) was measured at the 1‐year visit. Multiple linear regressions were performed to test the association between first‐year mean PA level, 1‐year visit GDF‐15 concentration and subsequent bodyweight changes. Mediation analyses were used to investigate whether GDF‐15 mediated the association between first‐year mean PA levels and consecutive bodyweight changes. Results: Multiple regression analyses demonstrated that higher first‐year mean PA levels significantly predicted lower GDF‐15 and bodyweight at 1 year (B = −2.22; SE = 0.79; P = 0.005). In addition, higher 1‐year visit GDF‐15 levels were associated with faster subsequent bodyweight loss (Time × GDF‐15 interaction B = −0.0004; SE = 0.0001; P = 0.003). Mediation analyses confirmed that GDF‐15 mediated the association between first‐year mean PA levels and subsequent bodyweight changes (mediated effect ab = 0.0018; bootstrap SE = 0.001; P < 0.05) and revealed that mean PA had no direct effect on subsequent bodyweight changes (c′ = 0.006; SE = 0.008; P > 0.05). Conclusions: This study suggests that GDF‐15 may be one of the molecules mediating the link between PA and late‐life weight loss, but mechanistic studies are necessary to further support the present findings.